Landscape as Heritage in the province of Chañaral, Atacama region, Chile - Palacios, Sebastian (2022)
To understand the landscape as heritage is to recognize it in a synthesizing condition, as a complex system of ecological, historical and social legacies. This approach allows an articulation and reading of the territory not as a sum of particularities but rather as a particular system, where the landscape, as a collective construction of society, is not only understood as a material construction, but also as a construction of memory and cultural expressions, which in the Atacama Desert have become evident with a clear mining emphasis, temporally since pre-Columbian times and spatially throughout the transversality, longitudinality and altitudinal levels of the territory. Cover image: Memorial site. “Animita”, 2017 - photo by Sebastian Palacios